Site and size of multiple sclerosis lesions predict enhanced or decreased female orgasmic function - Winder, Klemens; Seifert, Frank; Koehn, Julia; Deutsch, Martina; Engelhorn, Tobias; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf; Hilz, Max-Josef (Journal of Neurology, 2015)
Neuroimaging identified brain areas involved in female orgasm. In women with multiple sclerosis (MS), associations between orgasmic function and the site and size of MS-related magnetic resonance imaging (MRI) changes are undetermined. This study intended to correlate MS-associated cerebral lesion load and location with clinical scores of female orgasmic function. In 50 women with MS (mean age 37.0 ± 9.9 years), we assessed Female Sexual Function Index (FSFI) scores for orgasmic frequency, difficulty and satisfaction. We determined disease duration, Expanded Disability Status Scale (EDSS) scores, and cerebral MS-lesion load and location using T2-weighed 1.5 T MRIs. We correlated FSFI scores for orgasm with patient age, disease duration, EDSS scores, and cerebral MS-lesion load (Spearman rank correlation; significance: p < 0.05). FSFI scores for orgasm correlated inversely with MS-lesion load in the left temporal periventricular white matter and right middle-inferior occipital area, but directly with MS-lesion load in the right frontal primary motor cortex, left prefrontal/inferior frontal cortex, right amygdala, left temporal middle-inferior and fusiform areas, and midbrain. FSFI scores for orgasm did not correlate with patient age, disease duration and EDSS scores (p > 0.05). In conclusion, our results indicate that MS-lesions in left temporal periventricular and right visual association areas deteriorate orgasmic function. In contrast, direct correlations between frontotemporal or midbrain lesions and higher FSFI scores, indicating enhanced or disinhibited orgasmic function, suggest that these brain regions normally buffer orgasmic responses. Moreover, our results indicate that orgasmic dysfunction in women with MS evolves independently of disease duration and physical disability.
EVALuna2:22361